KATA-KATA TABU DALAM BAHASA MELAYU DIALEK KAPUAS HULU DI SEMANGUT: KAJIAN SOSIOLINGUISTIK - Asniwati, Asniwati; Madeten, Sisilya Saman; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of the study was to document and describe of taboo word in BMDKS based the classification on the opinion of Frazer and describe of reference euphemism based on the opinions Wijana and Rohmadi. The method used in the study is descriptive  the with of qualitative research. Using the sociolinguistic approach. Techniques data collection in the research this is techniques direct observation. Collection data tools in this research is recorders voice,  stationery to take notes, and researchers as the main instruments. The data source of this research is three informants  speech BMDKS. Based on the results of the research found 58 the words taboo BMDKS. The units linggual language a divided in  two the types, namely words and phrases that can be grauped to several categories such as: 1) the word based on the verb, Nouns, and adjectives,  2) the phrase in the units grammatical consisting of two or more words classified based phrase the category apositive the phrase type verbs, Adjectives,  and nouns. Based classification taboo that is; name of people and animals, parents name, name relatives, and taboo certain words the which elaborated again to be eight categories that is taboo the mention; genitals, sexual activity,  profession, physical functions, spirit, objects or circumstances, and diseases. Euphemisms references can be classified to be nine categories namely;  conditions, animals, spirit, objects, body parts, kinship, activity, profession, and disease.Keywords: the word taboo dialect Kapuas Hulu, reference euphemism, sociolinguistic